On some multilinear type integral systems. (September 2020) - Pezzolo, Fabio
Abstract: In this paper we prove some Liouville theorems for systems of integral equations related to Beckner and Stein–Weiss inequalities on R N . We consider both variational and non-variational solutions. In order to study the first type of solutions we applied Rellich type identities.